Heterogeneous Two-Region Model for Low-Aspect-Ratio Fixed-Bed Catalytic Reactors. Analysis of Fluid-Convective Contributions - Asensio, Daniela Anabel (2014)
ABSTRACT: A two-region, two-dimensional (2R2D) model aimed at improving the heat transfer description of multitubular catalytic reactors is introduced here. The effects concentrated in the wall thermal resistance (1/hw) of the standard 2D model (S2D model) are distributed in a fluid channel from the wall up to a distance of half-particle diameter and in the particle layer against the wall. The use of computational fluid dynamics (CFD) on regular arrays allowed estimations of two of the 2R2D key parameters: the heat transfer coefficient between wall and core channels hf and the ?true? wall-to-fluid coefficient hwf. The 2R2D and S2D models are compared at conditions when fluid mechanisms dominate radial heat exchange and reversible or irreversible catalytic reactions are carried out. The case of NH3 synthesis was taken as a basis of comparison. Significant differences are obtained in temperature predictions within the usual range of the tube-to-particle diameter ratio, 5 < N < 10, mainly for irreversible kinetics.